A computed tomographic evaluation of effect of mandibular advancement device at two different horizontal jaw positions in patients with obstructive sleep apnea - Pooran Chand; Neeti Solanki; Balendra Pratap Singh; Sunit Kumar Jurel; Surya Kant; Pranjali Dutt (Elsevier, 2023)
Statement of problem: Studies pertaining to the objective assessments of the efficacy of mandibular advancement device in patients with obstructive sleep apnea are scarce. Purpose: The purpose of this clinical study was to evaluate the effect of MAD at two different horizontal positions of mandible on upper airway dimensions through computed tomography. Material and methods: Twenty-nine consenting participants satisfying predetermined inclusion and exclusion criteria were enrolled and an adjustable two-piece MAD was fabricated at 50% maximum mandibular protrusion and after 4 weeks was adjusted to 70% protrusion. CT scans were obtained at baseline, 4 weeks after delivering MAD with 50% mandibular protrusion, and then after 4 weeks with 70% mandibular protrusion. Cross sectional area with diameters (lateral and anteroposterior) of upper airway was measured at three specific anatomic levels (retropalatal-RP, retroglossal-RG, and epiglottal-EG). Data were analyzed using the Student t-test for parametric analysis. Results: Intragroup comparison revealed a statistically significant increase in lateral & anteroposterior dimensions as well as cross sectional area at all three anatomical levels at 4 weeks after MAD with 50% mandibular protrusion compared with baseline and 4 weeks after MAD with 70% mandibular protrusion compared with baseline. However, the difference between lateral and anteroposterior dimensions with MAD at 70% protrusion compared with MAD at 50% protrusion was not statistically significant. The difference between cross-sectional area was found to be statistically significant. Conclusion: Mandibular advancement device at 70% mandibular protrusion is more effective compared with the device at 50% protrusion in relieving oropharyngeal obstruction seen in OSA.